Design of an additional safety rod for Ghana Research Reactor-1 using MCNP5 code - Boffie, J.; Odoi, H.C.; Akaho, E.H.K.; Nyarko, B.J.B.; Tuffour-Achampong, K. (Nuclear Engineering and Design, 2012)
In many licensed reactors, there are both control rods and shutdown or safety rods with the latter specifically designed for rapid shutdown of the chain reaction. But Ghana's Research Reactor 1 (GHARR-1), which is a Miniature Neutron Source Reactor (MNSR) has one control rod which serves the purpose of both reactivity control and shutdown of the reactor. This work presents an investigative study into the design of an additional safety rod, which will be an important safety component in the MNSR and will provide another alternative way to emergently shut down the reactor. The Monte Carlo Neutron Particle code; version 5, (MCNP5) was used to design the additional safety rod at one of the inner irradiation sites with cadmium as absorber material and stainless steel as clad. The irradiation site housing the safety rod was then enlarged, which affected the criticality of the core and a larger cadmium safety rod was inserted. In another instance, boron carbide was used as the absorber material also with stainless steel clad but without the further increment. After simulation, the cadmium safety rod, worth 2.94 mk could not shut down the reactor on insertion. However, the larger cadmium safety rod and the boron carbide safety rod of worth 4.54 mk and 5.90 mk respectively, attained subcriticality on insertion. The results indicate that an additional safety rod with boron carbide as absorber material can be used to enhance the safety of MNSRs. © 2012 Elsevier B.V. All rights reserved.
Keywords: safety rods; Miniature Neutron Source Reactor (MNSR); Ghana's Research Reactor 1 (GHARR-1); Monte Carlo Neutron Particle code; version 5, (MCNP5)